82.0k views
2 votes
Write the function rule for the function shown below reflected in the given axis.

​f(x)​x; ​-axis

Let​ g(x) be the reflection of​ f(x) in the ​-axis. What is the function rule for​ g(x)?

​g(x)

nothing

User Krugloid
by
6.0k points

1 Answer

4 votes

Answer:

The answer is "
\bold{g(x) = -(1)/(2x) \ and \ g(x)= -3x-12}".

Explanation:

Please find the complete question in the attached file.


\to f(x) = 4x

Following the y-axis reflexion, f(x) is 4(-x) = -4x after a
(1)/(8) vertical compression factor, f(x) is
(1)/(8) * -4x = (1)/(-2x)

So, the
g(x) = - (1)/(2x)

The y axis reflecting indicates that its entire function is multiplied by -1

so,
f(x)=3x+12^(-1)


\to g(x)=-3x-12

Write the function rule for the function shown below reflected in the given axis. ​f-example-1
User Reo Katoa
by
5.9k points